Environmental legislation awareness among construction contractors in Malaysia / Roseline Ikau and Corina Joseph - Ikau, Roseline; Joseph, Corina (Universiti Teknologi MARA Cawangan Sarawak, 2017)
Waste is mostly contributed by the construction industry. There is growing importance in the strategies to minimize waste at construction sites. This study aimed to determine the level of awareness on environmental legislation's among construction players in Malaysia. From October 2015 to March 2016, questionnaires were distributed to 306 Malaysian contractors who were engaged in various types of construction projects in Malaysia. The findings found that the level of awareness on environmental legislation's among the respondents was quite moderate, which was possibly explained by the coercive and normative isomorphism tenets. Several insights for further work are provided in this paper.